Pengaruh Strategi Penjualan Buku melalui Akad Khiyar terhadap Kepuasan Konsumen (Studi Kasus pada Toko Buku H. Minan Babat Lamongan) - Imro’atul Magfiroh; Abdullah Zawawi (Al-Maqashid: Journal of Economics and Islamic Business, 2022)
In an effort to improve good customer service, sellers must have the ability and must be able to create a sense of responsibility to consumers in order to create good expertise in the field of customer service. By holding a khiyar contract, consumers will feel satisfied because they can choose the desired product and do not feel disadvantaged. The method used in this study is a quantitative experiment with the formulation of the problem "How is the implementation of the book selling strategy on consumer satisfaction?" Then the second problem formulation is "How does the strategy of selling books through the khiyar contract affect consumer satisfaction?" As for the results of the research: first, that the H. Minan bookstore always provides good service to its consumers by giving time to choose the desired items. Second, that the influence of the book selling strategy through the Khiyar contract is quite large on consumer satisfaction at the H. Minan Babat Lamongan store. Because based on simple regression analysis Y = 3.236 + 0.824 X. The value of 4.06 is the constant value (a). The value of 0.824 is a regression coefficient, which means that any addition of 1. large enough to customer satisfaction.